Prevalence of the MDR1 gene mutation in herding dog breeds and Thai Ridgebacks in Thailand - Chommanad Lerdkrai (Veterinary World, 2021)
Background and Aim: A canine multi-drug resistance 1 (MDR1) nt230(del4) is a well-known inherited disorder that primarily affects collies and various herding breeds. The most recognized clinical implication for affected dogs is associated with an increased risk of multiple drug toxicity. To date, MDR1 gene mutations have been identified globally, especially in dogs from the USA and European countries. This study aimed to investigate the prevalence of MDR1 nt230(del4) in herding dog breeds and Thai Ridgebacks in Thailand.